Current developments in biotechnology and bioengineering : current advances in solid-state fermentation - Pandey, Ashok; Larroche, Christian; Soccol, Carlos Ricardo (Elsevier, 2017)
Current Developments in Biotechnology and Bioengineering: Current Advances in Solid-State Fermentation provides knowledge and information on solid-state fermentation involving the basics of microbiology, biochemistry, molecular biology, genetics and principles of genetic engineering, metabolic engineering and biochemical engineering. This volume of the series is on Solid-State fermentation (SSF), which would cover the basic and applied aspects of SSF processes, including engineering aspects such as design of bioreactors in SSF. The book offers a pool of knowledge on biochemical and microbiological aspects as well as chemical and biological engineering aspects of SSF to provide an integrated knowledge and version to the readers.